Effect of body size and intensive blood pressure management on cardiovascular and serious adverse events. Issue 5 (12th January 2022) - Pei, Junyu; Wang, Xiaopu; Zheng, Keyang; Su, Wen; Hu, Xinqun
Abstract : Background: Previous studies have shown that obese hypertensive patients have a lower risk of cardiovascular events than normal-weight patients, and that the performed hypertension treatment affects cardiovascular outcomes depending on the patient's body size. This study aimed to investigate the relationship between the BMI and cardiovascular outcomes and safety endpoints in hypertensive patients with intensive or standard blood pressure (BP) management. Methods: We used data from the Systolic Blood Pressure Intervention Trial (SPRINT). Cox proportional hazards models were used to analyze the data. The primary endpoint was cardiovascular disease (CVD) death, and the safety endpoint was serious adverse events. Results: In total, 9284 patients were included in our analysis. Thirty-seven patients in the intensive arm and 65 patients in the standard arm had CVD death. After multivariable adjustment, the BMI was not associated with the incidence of CVD death in the standard arm [hazard ratio 0.96, 95% confidence interval (CI) 0.91–1.02]. In the intensive arm, the incidence of CVD death decreased (hazard ratio 0.86, 95% CI 0.78–0.96) first and, then, increased (hazard ratio 1.15, 95% CI 1.07–1.25) with an increase in the BMI (inflection point, 32.33 kg/m 2 ). Conclusion: Intensive BP management in overweight, class I, and class II obese patients significantly reduced the cardiovascular outcomes without increasing the safety risks. Nevertheless, further clinical evidence is needed to verify the effectiveness of intensive BP management in patients with normal weight and class III obesity.